NF-κB inhibition impairs the radioresponse of hypoxic EMT-6 tumour cells through downregulation of inducible nitric oxide synthase - Ridder, M De (Nature Publishing Group, 2003)
Hypoxic EMT-6 tumour cells displayed a high level of inducible nitric oxide synthase (iNOS) and an increased radiosensitivity after a 16 h exposure to lipopolysaccharide, a known activator of nuclear factor-κB (NF-κB). Both iNOS activation and radioresponse were impaired by the NF-κB inhibitors phenylarsine oxide and lactacystin. Contrasting to other studies, our data show that inhibition of NF-κB may impair the radioresponse of tumour cells through downregulation of iNOS.